Broad-Spectrum Activity of Small Molecules Acting against Influenza a Virus: Biological and Computational Studies - Mariangela Agamennone; Fabiana Superti (MDPI AG, 2022)
Influenza still represents a problematic disease, involving millions of people every year and causing hundreds of thousands of deaths. Only a few drugs are clinically available. The search for an effective weapon is still ongoing. In this scenario, we recently identified new drug-like compounds with antiviral activity toward two A/H1N1 Influenza virus strains, which were demonstrated to interfere with the processes mediated by hemagglutinin (HA). In the present work, the compound's ability to act against the A/H3N2 viral strain has been evaluated in hemagglutination inhibition (HI) assays. Two of the five tested compounds were also active toward the A/H3N2 Influenza virus. To validate the scaffold activity, analogue compounds of two broad-spectrum molecules were selected and purchased for HI testing on both A/H1N1 and A/H3N2 Influenza viruses. Forty-three compounds were tested, and four proved to be active toward all three viral strains. A computational study has been carried out to depict the HA binding process of the most interesting compounds.